Relations of COVID-19-Related Stressors and Social Support With Chinese College Students' Psychological Response During the COVID-19 Pandemic - Li, Xiaoshan; Wu, Hou; Meng, Feifei; Li, Li; Wang, Yitong; Zhou, Mingjie (Frontiers in Psychiatry, 2020)
This study examined the main and interactive relations of stressors and social support with Chinese college students’ psychological symptoms (e.g., anxiety, depression) during the corona virus disease 19 (COVID-19) epidemic in 2020. All the constructs were assessed by self-report in an anonymous survey during the epidemic outbreak. Results showed that the number of stressors had a positive relation with psychological symptoms, while social support had a negative relation with psychological symptoms. In addition, social support served as a buffer against the negative impact of stressors. These findings hold implications for university counseling services during times of acute, large-scale stressors. In particular, effective screening procedures should be developed to identity students who experience a large number of stressors and provided suitable psychological intervention for them.